(untitled) (Muitas Vozes, 2021)
This article is of a sociolinguistic nature (LABOV, 2008 [1972]) and proposes to investigate the variable realization of the diphthong /ow/ in a speech sample of the Praça 14 de Janeiro, in Manaus (AM). The corpus was taken from a database made up of six sociolinguistic interviews with informants divided into three age groups: 18 to 35 years old, 36 to 55 and 56 onwards, one man and one woman for each age group, all with 4 to 8 years of schooling. For data analysis, the statistical software GoldVarb X (SANKOFF; TAGLIAMONTE; SMITH, 2005) was used, and the linguistic variables diphthong position in the word, stress, word class and following context, and the social variables sex and age group were controlled. The results demonstrated that the monophthongization of the diphthong /ow/ has not yet consolidated in our speech sample, since it occurred in 65.1% of the data, being in variation with its maintenance (34.9%).Of the controlled variables that are shown to act in the reduction of diphthong, the software selected, in order of relevance, age group, next context, sex and stress.